Commercial Gestational Surrogacy: Unravelling the threads between reproductive tourism and child trafficking - Hyder-Rahman, Nishat (Anti-Trafficking Review, 2021)
Narratives of commercial gestational surrogacy (CGS) as ‘baby-selling’ often conflate or interchange the transfer of children born via surrogacy with trafficking in children or the sale of children, two sometimes overlapping but nonetheless distinct offenses. Moreover, anti-trafficking laws have been used to police cross-border CGS. But when do CGS arrangements fall within the category of legitimate ‘reproductive tourism’ and when do they amount to child trafficking? In this paper I critically explore intersections between human trafficking laws and CGS, vis-à-vis the child, charting the relevant trafficking laws in the context of international surrogacy, and analysing whether trafficking laws are an appropriate mechanism through which to regulate CGS. I conclude that while child trafficking might occur via surrogacy, CGS in itself is not child trafficking under international law.